Utilizing noncatalytic ACE2 protein mutant as a competitive inhibitor to treat SARS-CoV-2 infection - Liu, Shengjiang; Chen, Haifeng; Chen, Xiangqun; Luo, Ningguang; Peraramelli, Sameera; Gong, Xiaoming; Zhang, Mingwei John; Ou, Li (Frontiers in Immunology, 2024)
Introduction Angiotensin converting-enzyme 2 (ACE2) is an enzyme catalyzing the conversion of angiotensin 2 into angiotensin 1-7. ACE2 also serves as the receptor of several coronaviruses, including SARS-CoV-1 and SARS-CoV-2. Therefore, ACE2 could be utilized as a therapeutic target for treating these coronaviruses, ideally lacking enzymatic function. Methods Based on structural analysis, specific mutations were introduced to generate mutants of ACE2 and ACE2-Fc (fusion protein of ACE2 and Fc region of IgG1). The enzyme activity, binding affinity, and neutralization abilities were measured. Results and discussion As predicted, five mutants (AMI081, AMI082, AMI083, AMI084, AMI090) have completely depleted ACE2 enzymatic activities. More importantly, enzyme-linked receptor-ligand assay (ELRLA) and surface plasmon resonance (SPR) results showed that 2 mutants (AMI082, AMI090) maintained binding activity to the viral spike proteins of SARS-CoV-1 and SARS-CoV-2. In An in vitro neutralization experiment using a pseudovirus, SARS-CoV-2 S1 spike protein-packed lentivirus particles, was also performed, showing that AMI082 and AMI090 significantly reduced GFP transgene expression. Further, in vitro virulent neutralization assays using SARS-CoV-2 (strain name: USA-WA1/2020) showed that AMI082 and AMI090 had remarkable inhibitory effects, indicated by comparable IC50 to wildtype ACE2 (5.33 µg/mL). In addition to the direct administration of mutant proteins, an alternative strategy for treating COVID-19 is through AAV delivery to achieve long-lasting effects. Therefore, AAV5 encoding AMI082 and AMI090 were packaged and transgene expression was assessed. In summary, these ACE2 mutants represent a novel approach to prevent or treat COVID-19 and other viruses with the same spike protein.